Estimation of bone mineral density among type 2 diabetes mellitus patients in western Odisha - Thakur, Atanu Kumar; Dash, Satarupa (International Journal of Research in Medical Sciences, 2018)
Background: Diabetes Mellitus is one of the most common chronic non-communicable diseases in the world. The relationship between type 2 diabetes mellitus (T2DM) and bone mineral density (BMD) has been controversial. Early identification of reduction in bone mass in a diabetic patient may be helpful in preventing the bone loss and future fracture risks. Objective: The aim is to study the effect of T2DM on BMD among patients in western Odisha. Methods: A cross-sectional study was conducted on 120 patients between 40 and 65 years of age which included 60 diabetic and 60 nondiabetic subjects. BMD was measured using qualitative ultrasound and the data were compared among age-matched subjects of both the groups. Statistical analysis was performed using unpaired Student’s t-test and test of equality of proportions. Results: No significant difference was observed in bone density of both the groups. On further analyzing the data, incidence of osteoporosis was higher among diabetic subjects, whereas incidence of osteopenia was higher among nondiabetic subjects. Conclusions: Although significant difference in bone mineral density was not observed in both the groups, the incidence of osteoporosis was higher among type 2 diabetics. Hence, all type 2 diabetics should be evaluated for the risk of osteoporosis and should be offered appropriate preventive measures.